The literary workshop as a pedagogical strategy in the classroom - Peraza Rodríguez, Mario (Rastros Rostros, 2020)
The subject of this article addresses the literary workshop as a didactic device in the teaching of literature supported by sufficient theoretical and methodological supports that clearly support its development in the classroom. Since the development of the research project of Master in Pedagogy of the District University, whose name is “Creation from the autobiographical chronicle: a strategy for the development of literary education.” Findings are found in which they demonstrate certain ambiguities regarding the skills that the literary workshop strengthens, as well as the almost exclusive focus on reading, suppressing to some extent the creative writing processes in relation to an implicit methodological framework that due to its Informality cannot contribute to the development of the workshop as an organized pedagogical device. There are multiple voices that have spoken about the literary workshop: some from their experience in the development of these spaces for literary creation; others from the literary reading workshop in formal school settings; many others, from a point of view of the training of writers and the problem of the teachability of literature as a professional training career. Gianni Rodari (1973), Louise Rosenblatt (1978), Benigno Delmiro Coto (2001), and finally, Teresa Colomer (2001). Likewise, other proposals such as the creative writing workshops by RELATA (Ministerio de Cultura, 2010), show ways of systematizing literary artistic practice. This work dialogues from perspectives generating strategies that unite the literary creation workshop and the pedagogical workshop in the context of the Pedagogy of Literature.